2020
DOI: 10.3389/fmicb.2020.00692
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into Function and Subcellular Localization of Plasmopara viticola Putative RxLR Effectors

Abstract: Grapevine downy mildew, caused by oomycete fungus Plasmopara viticola, is one of the most devastating diseases of grapes across the major production regions of the world. Although many putative effector molecules have been identified from this pathogen, the functions of the majority of these are still unknown. In this study, we analyzed the potential function of 26 P. viticola effectors from the highly virulent strain YL. Using transient expression in leaf cells of the tobacco Nicotiana benthamiana, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Previously, we identified several P. viticola RxLR effectors capable of triggering cell death when expressed transiently in N. benthamiana cells. Our preliminary results suggested that among these effectors, PvAVH53 and PvAVH54804 induced cell death the most rapidly and at the lowest apparent concentration 33 . Imaging of N. benthamiana protoplasts transiently expressing PvAVH53-GFP or PvAVH54804-GFP showed that PvAVH53-GFP localizes to the nucleus, whereas PvAVH54804-GFP accumulates in both the nucleus and cytoplasm (Fig.…”
Section: Nuclear Localization Of Pvavh53 Is Essential For Triggering mentioning
confidence: 74%
See 4 more Smart Citations
“…Previously, we identified several P. viticola RxLR effectors capable of triggering cell death when expressed transiently in N. benthamiana cells. Our preliminary results suggested that among these effectors, PvAVH53 and PvAVH54804 induced cell death the most rapidly and at the lowest apparent concentration 33 . Imaging of N. benthamiana protoplasts transiently expressing PvAVH53-GFP or PvAVH54804-GFP showed that PvAVH53-GFP localizes to the nucleus, whereas PvAVH54804-GFP accumulates in both the nucleus and cytoplasm (Fig.…”
Section: Nuclear Localization Of Pvavh53 Is Essential For Triggering mentioning
confidence: 74%
“…Previous experiments have indicated that the P. viticola effectors PvAVH53 and PvAVH54804 can induce cell death in N. benthamiana and are localized strictly in the nucleus or both in the nucleus and cytoplasm, respectively 33 . Our experiments further showed that PvAVH53 and PvAVH54804 induce cell death in N. benthamiana.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations